2016
DOI: 10.3109/07420528.2015.1119158
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of blue-light shield eyewear for adults against light pollution from self-luminous devices used at night

Abstract: We investigated sleep quality and melatonin in 12 adults who wore blue-light shield or control eyewear 2 hours before sleep while using a self-luminous portable device, and assessed visual quality for the two eyewear types. Overnight melatonin secretion was significantly higher after using the blue-light shield (P < 0.05) than with the control eyewear. Sleep efficacy and sleep latency were significantly superior for wearers of the blue-light shield (P < 0.05 for both), and this group reported greater sleepines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 24 publications
4
64
0
1
Order By: Relevance
“…A simple solution that may effectively block and reduce the blue portion of the light spectrum before bedtime are blue light blocking glasses and lenses . Wearing blue light blocking eyewear before and during bed time may effectively attenuate LED induced melatonin suppression and thus can potentially facilitate the adaption to new social schedules and reduce sleep disturbances and their consequences among the general population. Further, a reduction of the blue portion in artificial light during nighttime hours could protect shift workers against disorders such as cancer and cardiovascular disorders.…”
Section: Countermeasures For the Altering Effects Of The Blue Lightmentioning
confidence: 99%
“…A simple solution that may effectively block and reduce the blue portion of the light spectrum before bedtime are blue light blocking glasses and lenses . Wearing blue light blocking eyewear before and during bed time may effectively attenuate LED induced melatonin suppression and thus can potentially facilitate the adaption to new social schedules and reduce sleep disturbances and their consequences among the general population. Further, a reduction of the blue portion in artificial light during nighttime hours could protect shift workers against disorders such as cancer and cardiovascular disorders.…”
Section: Countermeasures For the Altering Effects Of The Blue Lightmentioning
confidence: 99%
“…They may be partly due to small sample sizes, given that many studies have been of fewer than 20 subjects. In addition, the effects of light at night on sleep and alertness can depend on the spectra (Ayaki et al, 2016;Chellappa et al, 2013;Santhi et al, 2012), timing (Carrier & Dumont, 1995), duration (Chang et al, 2012), and intensity (Cajochen et al, 2000) of the light exposure, as well as prior exposure to light (Chang et al, 2013;Chang, Scheer, & Czeisler, 2011). It is therefore critically important for studies to report this information to facilitate comparisons between studies and replication of research.…”
Section: Laboratory-based Sleep Studies: Mechanisms and Physiologymentioning
confidence: 99%
“…Since blue wavelengths of light have the greatest impact on melatonin and circadian rhythms, reducing or filtering out these wavelengths could also reduce impacts of ALAN on sleep. However, studies testing this approach for humans have reported mixed results (Ayaki et al, 2016;Heath et al, 2014;van der Lely et al, 2015), and little is known about whether it would benefit wildlife (Dimovski & Robert, 2018). Other possible solutions include dimming lights or simply switching them off when they are of least benefit to humans (Davies & Smyth 2018).…”
Section: Investigating How Ecologically Relevant Alan Affects Sleep Ismentioning
confidence: 99%
“…Blue light in the range of wavelengths 446–477 nm has been identified as the most potent light stimulus that suppresses melatonin production,2 a hormone that plays a major role in the regulation of sleep and wake cycles 3. Accordingly, Twilight filters the blue light emitted from mobile devices and protects the eyes with a soft red pellicle, potentially helping the user to fall asleep earlier and sleep better 1 4 5. On the basis of the user's local geographic coordinates, which are taken by the app to set sunrise and sunset times automatically, the filter intensity is smoothly adjusted when darkness falls.…”
Section: About the Appmentioning
confidence: 99%
“…In this regard, Twilight app may be particularly valuable, assisting athletes in avoiding blue-light exposure; sleeping earlier and better as a consequence. Indeed, the protective effect of blue-light shields on sleep quality has been previously demonstrated,4 5 making the adoption of such technology promising. However, whether the Twilight app can actually improve athletes’ recovery is another question, and requires new scientific investigations.…”
Section: Use In Clinical Practicementioning
confidence: 99%